URGENSI PERLINDUNGAN HUKUM BAGI PEMBELA HAK ASASI MANUSIA (HUMAN RIGHTS DEFENDER) DI INDONESIA - Rahayu Rahayu (Faculty of Law, Universitas Diponegoro, 2010)
Human rights defenders are they working and having activities dealing with any effort to promote human rights. They stand in the front tine of struggle and dignifying human rights to utter the victims of human rights violation (the voice of the voiceless). Their existence is obviously recognized in United Nations' Genera! Assembly Nr. 53/144 on